Analysis of anti-collision performance of a new assembled rolling guardrail. (January 2023) - Yao, Juncheng; Zhang, Jinpeng; Huang, Liang; Xu, Jianguo; wang, Bo
Abstract: Bridge guardrails play an important role in vehicle safety. Bridge guardrails frequently use concrete guardrails and beam-column guardrails. However, they have the disadvantages of poor buffering effect, being difficult to replace after damage, and being easy to cause damage to the bridge. A novel style of assembled rolling guardrail is presented in light of these drawbacks. In this research, a vehicle-guardrail collision numerical model is built in LS-DYNA. Subsequently, the performance of Beam-column guardrail (B-C.G), Assembled Guardrail (A.G), and Assembled rolling guardrail (A-R.G) is evaluated. The findings demonstrate that the A-R.G satisfies the specification's requirements, can increase the construction efficiency, and, in contrast to the conventional beam-column guardrail, essentially does not cause damage to the bridge. Additionally, it performs better than the other two types of guardrails. Compared with the A.G and the B-C.G, the A-R.G has better energy absorption effect, steering effect. Moreover, the A-R.G significantly reduces the acceleration of the vehicle. The A-R.G dramatically lessens guardrail and vehicle damage, enhances the guardrail's structural integrity, and increases passenger safety.